Associations of serum citrate levels with knee structural changes and cartilage enzymes in patients with knee osteoarthritis. (19th January 2020) - Bian, Fuqin; Ruan, Guangfeng; Xu, Jianhua; Wang, Kang; Wu, Juan; Ren, Jiale; Chang, Bingru; Ding, Changhai
Abstract: Objective: The aim of this study was to investigate cross‐sectional associations between serum levels of citrate and knee structural changes and cartilage enzymes in patients with knee osteoarthritis (OA). Method: A total of 137 subjects with symptomatic knee OA (mean age 55.0 years, range 34‐74, 84% female) were included. Knee radiography was used to assess knee osteophytes, joint space narrowing (JSN) and radiographic OA assessed by Kellgren‐Lawrence (K‐L) grading system. T2‐weighted fat‐suppressed fast spin echo magnetic resonance imaging (MRI) was used to determine knee cartilage defects, bone marrow lesions (BMLs) and infrapatellar fat pad (IPFP) signal intensity alternations. Colorimetric fluorescence was used to measure the serum levels of citrate. Enzyme‐linked immunosorbent assay was used to measure the serum cartilage enzymes including matrix metalloproteinase (MMP)‐3 and MMP‐13. Results: After adjustment for potential confounders (age, sex, body mass index), serum citrate was negatively associated with knee osteophytes at the femoral site, cartilage defects at medial femoral site, total cartilage defects, and total BMLs (odds ratio [OR] 0.17‐0.30, all P  < .05). Meanwhile, serum citrate was negatively associated with IPFP signal intensity alteration (OR 0.30, P  = .05) in multivariable analyses. Serum citrate was significantly and negatively associated with MMP‐13 (β −3106.37, P  < .05) after adjustment for potential confounders. However, citrate was not significantly associated with MMP‐3 in patients with knee OA. Conclusion: Serum citrate was negatively associated with knee structural changes including femoral osteophytes, cartilage defects, and BMLs and also serum MMP‐13 in patients with knee OA, suggesting that low serum citrate may be a potential indicator for advanced knee OA.